Influence Of Micro-Aggression As Barriers In Knowledge Acquisition And Academic Performance Among Youth - Bussa Siva Chaithanya; Mandula Ramya sri; Lanka Shiva Leela Parvathi; Buddini Sai Sowmya (Help: Journal of Community Service, 2024)
A micro aggression is an indirect and unintentional discrimination against members, people commits micro aggression against others. This study looks into the complex interactions between microaggressions and how they affect young people's learning and academic achievement. Due to their widespread occurrence in a variety of social circumstances, microaggressions subtle and frequently inadvertent acts of bigotry or prejudice have drawn a lot of attention recently. Even though they seem harmless, microaggressions can seriously impair young people's educational experiences, making it more difficult for them to learn new things and achieve academic success. Using an analysis of the body of research, this study investigates the various ways that microaggressions occur in educational environments and the harm they cause to young people. It looks at how these small acts of discrimination lead to the building of barriers that obstruct learning and academic accomplishment by using a critical lens. Additionally, the research explores the psychological mechanisms by which microaggressions function, including how they contribute to young people's emotions of impostor syndrome, marginalization, and stereotype threat. In addition, this study explores the intersections between microaggressions and a range of social identities, including socioeconomic class, gender, color, and ethnicity. It does this to show how these encounters affect young people differently in different ways. Additionally, it looks at the structural causes of the persistence of microaggressions in educational settings and considers various approaches to lessen their impact and promote inclusive learning environments.